Paradigma Pedagógico Ignaciano para mejorar el desempeño de los docentes en la Unidad Educativa Fiscal Lauro Guerrero de la ciudad de Loja - Guerrero Jaramillo, Gloria Irene (2022)
At present, the Ignatian Pedagogical Paradigm represents an essentially humanistic action, based on liberating competencies and reflected in an integral education, where power, discipline, spirituality and the practice of values are combined in the educational field, responding to the current demands in the life of the human being; The main objective is to integrate the Ignatian pedagogical paradigm to improve the performance of Basic Education teachers in the Lauro Guerrero Educational Unit in the city of Loja, its purpose is to provide quality teaching with support material that leads to meaningful learning and improve the educational process. The present work was quantitative, which allowed strengthening the descriptive equitable work; the methods used were inductive-deductive, analytical and synthetic, which allowed collecting data to refine the research questions in the interpretation process; A survey was applied to 30 teachers, which allowed obtaining truthful data and identifying as very good the implementation of this pedagogical model within the institution, also they considered very good the practice of values where the results were favorable to determine each variable, in order to recognize the ideas in a constructive way about themselves, to strengthen their knowledge, which allows describing and analyzing the interrelationships to contribute significantly to the understanding of samples; Therefore, it is concluded that it is a good option to incorporate the Ignatian pedagogical paradigm that promotes a humanistic process, practice of values, active participation that responds to the needs, interests, rhythms and learning styles contributing to quality education. Keywords: paradigm pedagogical, humanist, comprehensive education, values, Ignatian.